Compressed Natural Gas Passenger Vehicle Development â€“ Issues and Challenges - Sahari, Barkawi; Ali, Yusoff; Ahmadun, Fakhru’l-Razi; Abdullah, Shahrir; Hassan, Masjuki; Aris, Ishak; Abdullah, Muhamad Adlan; Ahmad, Mohd. Fauzy; Chelliah, V.; Taha, Zahari; Aziz, Abd. Rashid; Musa, Md. Nor; et al. (2006)
The research and development of automotive vehicle has always been influenced by the availability and the form of fuel. The oil reserves are depleting by the day. This will affect the automotive designs, research and development. particularly, the engine and transmission, fuel storage and the vehicle body. For passenger car, either an alternative fuel need to be sought and utilised fully and/or new fuel need to be developed. In either cases, technological research and development on the engine and transmission, fuel storage and the vehicle body need to be carried out extensively. For this purpose, collaborative efforts between the Universities, Research Institutes and Industries and strong funding are required. This paper presents the results of the research and development program for the development of a Compressed Natural Gas (CNG) Direct Injection (DI) vehicle sponsored by the Ministry of Science, Technology and Innovation (MOSTI) under the Intensification of Research Priority Areas (IRPA) mechanism. It is a collaborative research program involving UPM, UM, UKM, PRSS, UTM, UiTM, UTP and PROTON. This paper also discusses the issues arising from the implementation of the programme, the challenges faced and the way forward for the CNG vehicle.